A DISCUSSION ON THE GOVERNMENT'S HANDLING OF THE FLOOD DISASTER IN NORTH SUMATRA ON TIKTOK - Uky Firmansyah Rahman Hakim; Kiki Rahmayani Hasibuan; Abdi Tanjung; Muhammad Abduh Isma; Abdul Kholik Harahap; Mhd. Irsan Fikli (Program Pascasarjana UIN Sumatera Utara, 2026)
The purpose of this study was to examine the discourse surrounding the government's handling of flood victims on TikTok. This research was descriptive qualitative, employing Robert N. Entman's framing analysis model. Data collection techniques included observation, documentation, and literature review. Data analysis techniques included examining the text, visuals, and narratives in TikTok content on the accounts @Kementrian Sosial RI, @Bobby Nasution, @Ferry Irwandi, and @CallMeHyung. Robert N. Entman's model analysis was used to identify how the media constructs an event through four main elements: defining problems, diagnosing causes, making moral judgments, and emphasizing solutions. The results of this study are as follows: 1) The discourse of flooding as an inevitable natural disaster. This study shows that flooding in TikTok reporting is constructed as a natural disaster caused by extreme weather factors, such as heavy rainfall and river overflows. This discourse positions flooding as a natural event beyond human control, so the focus of news coverage is directed at the impact and post-disaster management, rather than the structural causes. 2) The discourse of the government as the primary actor and helper. The dominant discourse in TikTok news coverage positions the government as the primary actor, present and acting swiftly in flood management. Video content consistently depicts the activities of government officials, officials, and volunteers involved in evacuating residents, distributing aid, and visiting affected locations. 3) The discourse of social concern and solidarity. The research also indicates the existence of a discourse of social concern and solidarity.